2021
DOI: 10.3390/healthcare9111418
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Training Load Variables in Elite Soccer Players U-14 throughout the Competition Season

Abstract: Excessive daily training load (TL) can affect the musculoskeletal system health of youth elite soccer players. The purposes of this study were (i) to describe the TL and session rating of perceived exertion (s-RPE) throughout the competition season; (ii) to analyze the weekly (w) differences of acute (daily) workload (wAWL), chronic workload (wCWL), acute–chronic workload ratio, training monotony (wTM), and training strain (wTS) among three periods over the season (early-, mid-, and end-season) by playing posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In the early-, mid-, and end-season, there was a large and negative relationship between Avg TD and DOMS, as well as between sleep and Avg HSRD. Similar to the results of this study, previous research has linked perceived sleep, stress, fatigue, and DOMS to daily perceived intensity at the professional level [38].…”
Section: Discussionsupporting
confidence: 90%
“…In the early-, mid-, and end-season, there was a large and negative relationship between Avg TD and DOMS, as well as between sleep and Avg HSRD. Similar to the results of this study, previous research has linked perceived sleep, stress, fatigue, and DOMS to daily perceived intensity at the professional level [38].…”
Section: Discussionsupporting
confidence: 90%
“…One potential reason for the decrease in COD ability towards the end of the season could be due to the higher AWL during the early-season compared to the endseason (1442.5 vs. 934.5). In a previous study by Nobari et al [40], the AWL was reported to be higher during the start of the season compared to the end of the season in youth soccer players (under-14). The higher load during the beginning of the season could be to prepare the players for the intensity of the upcoming season [41].…”
Section: Discussionmentioning
confidence: 78%
“…According to Nobari et al 8 , increasing internal intensity (e.g., HR and RPE) is linked to higher TM and TS, implying that increasing external intensity raises rating perceived. According to a previous studies 9 , 37 , 38 , an increase in TM can lead to overtraining, which is one of the consequences of a not well-adjusted training plan and, as a result, it raises the internal intensity during training and competition.…”
Section: Discussionmentioning
confidence: 99%